The strategic vision and its impact on the growth strategy of insurance companies: Applied research in the Iraqi General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The subject of the strategic vision is of great importance to all companies because they live in an environment of rapid change in various areas of life. Supports the performance of its operations in a better way, towards appropriate strategic growth and achieving success. The research aims to determine the level of interest of the researched company in the research variables (strategic vision and growth strategy), and the importance of the research came in being an attempt to provide the theoretical and scientific foundations for the research variables (strategic vision and growth strategy). As for the research method, it was relied on the descriptive analytical method, relying on the questionnaire as a means of obtaining data from the sample of (136) people who are in the functional level (department manager, assistant department manager, branch manager, assistant branch manager) in the Iraqi insurance company In general, and through the results achieved, it became clear that the strength of the impact of the strategic vision on the growth strategy is of a high amount, and based on this, the strategic vision derives its importance from the strength of Include it in the growth strategy and this is not consistent with the content of the main hypothesis. The research concluded that it is necessary to invest the influence relationship between the strategic vision and the growth strategy, because it has a role in achieving the company's future goals.